Survey on the Use of Derivatives in Indonesia - Lantara, I Wayan Nuka (Gadjah Mada International Journal of Business, 2010)
This paper provides survey evidence on the use of derivatives among firms listed on the Indonesian Stock Exchange. The finding shows that the participation rate in the use of derivatives is 28.8 percent, much lower than those found in developed countries. For the derivatives non-users, insignificant risk exposure is reported as the most important rationale for not using derivatives. Consumer goods industry constitutes the largest proportion of firms using derivatives. The majority of respondents utilize derivatives to hedge against financial risks rather than to speculate. Foreign currency risk and interest rate risk are the most important types of risks faced with by respondents. Using the Chi-square and the Fisherâs exact tests, the result corroborates the size effect hypothesis, where the use of derivatives is more popular among large firms than small firms. A SURVEY ON THE USE OF DERIVATIVES IN INDONESIAKeywords: derivatives; hedging; risk management